Hypermedia Prototype in Secondary School : Cell as a Basic Unit of Life - Rosmawani, Ibrahim (2004)
The purpose of this project to design and develop a hypermedia prototype on topics "Cell as a basic unit of life". The aim of the prototype was to introduce and consolidate the concept learnt on the topic for student in secondary school level (Form One until Form Three). Additionally, researcher have done some evaluation studies about the usability of the courseware. The prototype was develop using the entity-relationship (E-R) model Relationship Management Methodology (RMM) as a design tool.